Sea change [compact disc, unabridged] - Parker, Robert B., 1932-2010 (Parker, Robert B., 1932-2010. Jesse Stone novels., 2006)
Jesse Stone investigates the murder of a woman, who is found in a cove near Paradise, Massachusetts. This leads to a world of wealth and depravity centered on a couple of yacht owners from Florida and their crowd.